Psychometric Properties Of A Questionnaire To Assess Educational Inclusion From The Perception Of University Students (Journal of Pharmaceutical Negative Results, 2023)
Latin American higher education institutions have the constitutional and social mandate to generate changes in their organizational, relational and academic configuration. In this context, educational inclusion -understood in its broad sense and not only in diversity- constitutes one of the backbone paths to contribute to these high purposes. Thus, and by virtue of what has been expressed, this methodological study reports the psychometric properties of an instrument (developed by the first four authors of this article) to evaluate educational inclusion from the perception of university students. This instrument underwent content validation processes by a system of expert judges. The statistical validation of the questionnaire (44 items) was carried out on a sample of 175 volunteer students (74.3% women and 25.7% men) from a social management and development program at a state university located in Santa Elena (Ecuador); 38 items were accepted for the final version of the instrument. The analyses showed a high reliability (0.878) for the entire instrument and an adequate relationship and dependence between each of the 6 factors identified through factor analysis. It is concluded that the questionnaire is valid, reliable and relevant to be used for research, diagnosis and evaluation of the impact of institutional policies in the field of educational inclusion.